Impact on COVID-19 pandemic on children immunization coverage in Bulgaria - Valeriya Nikolova (Biotechnology & Biotechnological Equipment)
The primary focus of health systems on containing the COVID-19 epidemic impedes access to health care for society’s most vulnerable segments, particularly children. For years, Bulgaria experienced a decline in mandatory vaccine coverage in children, especially for measles, mumps and rubella. The study explored the impact of the COVID-19 pandemic on immunization coverage in Bulgarian children with diphtheria, tetanus, and pertussis-containing vaccine third dose (DTP3) and measles-containing vaccine first dose (MCV1) during the pandemic years, 2020-2022. We used ARIMA model to capture temporal trends in coverage with diphtheria, tetanus, and pertussis-containing vaccine third dose (DTP3) and measles-containing vaccine first dose (MCV1) in children from 2000 to 2019 (pre-pandemic period) to forecast expected coverage in 2020-2022 (pandemic period). The expected vaccination coverage, predicted by ARIMA models, with DTP3 and MCV1 during the whole pandemic period, except for DTP3 in 2022, was higher than the reported vaccination coverage. The observed MCV1 coverage in 2020 and 2021 was slightly below the lower confidence limit, most likely because of the COVID-19 pandemic. The study demonstrates that the COVID-19 pandemic has further exacerbated the problem of vaccine coverage with DTP3 and MCV1 among children in Bulgaria, especially with MCV1.